Inflatable Rockbolts at Otter-Juan Mine, Kambalda - Turner, M.H.; Green, T. (Deep Mining 2007: Proceedings of the Fourth International Seminar on Deep and High Stress Mining, 2007)
The Otter-Juan Mine in Kambalda, Western Australia is over 1350 m deep, with very high stresses and a weak ultramafic hangingwall. Support systems in the ore drives have to cope with severe deformations and seismicity. By mid-2005 the 2-pass support system of split sets and mesh followed by threadbars was becoming difficult to manage due to failure of split sets before the threadbars could be installed. Trials using inflatable rockbolts commenced in August 2005. The trials proved successful and the bolts were introduced as standard ore drive support in June 2006. The trials took far longer than expected due to supply delays and the necessary modifications to equipment required to ensure reliable installation.